Manajemen Risiko pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Solok - Diana Utami Arif Diana; Nofrivul Nofrivul; Rizal Rizal; Chitra Indah Sari (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The problem in this study is how to manage risk at the Solok Regency Amil Zakat Agency in identifying risks, analyzing risks and evaluating risks in the Solok Regency BAZNAS. The purpose of this study is to find out the risk management in the collection of zakat and the distribution of zakat in BAZNAS Solok Regency, including to know the constraints in the BAZNAS program of Solok Regency in risk management. The type of research that the author uses (field research) field research with qualitative descriptive methods. The data collection technique carried out by the author is interviews and documentation obtained from amil in BAZNAS Solok Regency. The results in the field can conclude that Risk Management, starting from the stages of risk assessment, risk identification, risk analysis, risk evaluation and risk mitigation. Risk Management Research, starting from the stages of risk assessment, risk identification, risk analysis, risk evaluation and risk mitigation. From these stages, risk identification to risk evaluation obtained 5 possible risks that can interfere with the performance and process of BAZNAS Solok Regency at any time.┬á The field of zakat collection in Solok regency high risk includes not achieving zakat, Muzakki Dissatisfaction medium risk includes limited access by Muzakki, low risk includes lack of manpower, lack of understanding of zakat.